Spinal Epidural Collection following Lumbar Puncture in a Patient with Idiopathic Intracranial Hypertension - Krothapalli, Neeharika; Hersh, David; Yorns, William; Acsadi, Gyula; DiMario, Francis J., Jr. (Journal of Pediatric Neurology, 2023)
Epidural cerebrospinal fluid (CSF) collections after lumbar puncture are a rare and underdiagnosed entity in the pediatric population. Physicians should maintain vigilance about warning signs of severe progressive back pain extending beyond the puncture site and new neurological symptoms after lumbar puncture. Extensive symptomatic epidural collections, which may be dorsal and compromise the thecal sac, can be secondary to CSF leakage. Early diagnosis with spinal magnetic resonance imaging and prompt treatment is vital in reducing morbidity and mortality. These collections typically resolve with conservative management and no serious sequelae. We report a rare case of spinal epidural collection following a lumbar puncture in a patient with idiopathic intracranial hypertension that was successfully treated with a blood patch and surgical decompression in the setting of significant neurological deterioration.
Keywords: lumbar puncture; epidural collection; idiopathic intracranial hypertension